2005
DOI: 10.1080/09513590500231627
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rosiglitazone and metformin on menstrual cyclicityand hirsutism in polycystic ovary syndrome

Abstract: Our data show that both metformin and rosiglitazone improve ovarian function and hirsutism in patients with PCOS. Rosiglitazone appears better than metformin in the treatment of hirsutism and has better patient tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 44 publications
3
54
1
4
Order By: Relevance
“…However, the estimated cost of glargine was $216 for 24 weeks, yet the average monthly cost of a vial is $70 (5). This results in a total cost of glargine therapy of $420 for 24 weeks.…”
Section: Marc De Hert MDmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the estimated cost of glargine was $216 for 24 weeks, yet the average monthly cost of a vial is $70 (5). This results in a total cost of glargine therapy of $420 for 24 weeks.…”
Section: Marc De Hert MDmentioning
confidence: 99%
“…Finally, such a combination may also provide some help to tackle other metabolic abnormalities of PCOS, like hirsutism and glucose intolerance (5,6 R osenstock et al (1) reported on the safety and efficacy of add-on insulin glargine versus rosiglitazone for patients with type 2 diabetes not adequately controlled on dual oral therapy with sulfonylurea plus metformin. The main finding of the study was similar glycemic control in both groups.…”
Section: Marc De Hert MDmentioning
confidence: 99%
See 1 more Smart Citation
“…Coadministration of pioglitazone with IGF-1 (5) might be a more optimal treatment strategy for patients with such extreme syndromes. We have recently reported on five patients with treatment-emergent diabetes who were successfully switched to a more suitable antipsychotic, which resulted in the reversal of diabetes (to risperidone in one patient [4] and amisulpride in four patients [5]). Since aripiprazole, a second-generation antipsychotic agent described as having a good metabolic profile (6 -8), became available on the Belgian market, all consecutive patients with recently detected diabetes were switched to this agent.…”
Section: Angela Napolimentioning
confidence: 99%
“…The central afferent visual function was evaluated via the delay of the major positive component (P100) of the visualevoked potentials that was generated following a pattern-reversal checkboard stimulation (5). Cardiovascular autonomic function was assessed by means of the five standard cardiovascular reflex tests (2,3,6).…”
mentioning
confidence: 99%